A Role for MAIT Cells in Colorectal Cancer - Berzins, Stuart P.; Wallace, Morgan E.; Kannourakis, George; Kelly, Jason (Frontiers in Immunology, 2020)
MAIT cells are MR1-restricted T cells that are well known for their anti-microbial properties, but they have recently been associated with different forms of cancer. Several studies have reported activated MAIT cells within the microenvironment of colorectal tumours, but there is conjecture about the nature of their response and whether they are contributing to anti-tumour immunity, or to the progression of the disease. We have reviewed the current state of knowledge about the role of MAIT cells in colorectal cancer, including their likely influence when activated and potential sources of stimulation in the tumour microenvironment. The prospects for MAIT cells being used in clinical settings as biomarkers or as targets of new immunotherapies designed to harness their function are discussed.